Toxicity of Some Insecticides on the Hymenopteran Parasitoid, Bracon Hebetor (Hymenoptera: Braconidae) - Ebeid, A.R; Elbehery, Huda H.; Farag, N.A.; Gesraha, M.A. (European Journal of Sustainable Development, 2017)
The present study showed the acute toxicity and the effects of two widely used insecticides Profenofos, Cyfluthrin and the IGR (Runner) on the activity of the larval parasitoid, Bracon hebetor (Hymenoptera: Braconidae), a natural enemy of many insect pests. The direct application of the tested insecticides induced drastic effect on the adult male and/or female parasitoid, leading to 100% mortality within 24-48 hours post treatment for Cyfluthrin, 7 days post treatment for Runner treatment and 6 days post treatment for Profenofos. The indirect effect bioassays were conducted by applying five concentrations of each insecticide to the artificial diet of the host larvae (Galleria mellonella). The least toxic one to B. hebetor was Profenofos followed by Runner. While Cyfluthrin was the most toxic one which was dangerous on all life stages of B. hebetor, influencing the number of laid eggs by the parasitoid, percent of pupation and leading to failure of adult emergence. Keywords: Bracon hebetor, Profenofos, Cyfluthrin, Runner